Causal analysis between altered levels of interleukins and obstructive sleep apnea - Yi, Minhan; Zhao, Wangcheng; Fei, Quanming; Tan, Yun; Liu, Kun; Chen, Ziliang; Zhang, Yuan (Frontiers in Immunology, 2022)
Background: Inflammation proteins including interleukins (ILs) have been reported to be related to obstructive sleep apnea(OSA). The aims of this study were to estimate the levels for several key interleukins in OSA, and the causal effects between them. Method: Weighted mean difference (WMD) was used to compare the expression differences of interleukins between OSA and control, and the changed levels during OSA treatments in the meta-analysis section. A two-sample Mendelian Randomization (MR) was used to estimate the causal directions and effect sizes between OSA risks and interleukins. The inverse-variance weighted (IVW) was used as the primary method followed by several other MR methods including MR Egger, Weighted median and MR-Robust Adjusted Profile Score as sensitivity analysis. Results: Nine different interleukins including IL-1β, IL-2, IL-4, IL-6, IL-8, IL-12, IL-17, IL-18 and IL-23 were elevated in OSA compared to control to varying degrees, ranging from 0.82 to 100.14 pg/ml, and one interleukin IL-10 was decreased by 0.77pg/ml. Increased IL-1β, IL-6, IL-8 rather than IL-10 can be reduced in OSA by effective treatments. Further, the MR analysis of the IVW method showed that there was no significant evidence to support the causal relationships between OSA and the nine interleukins including IL-1β, IL-2, IL-4, IL-5, IL-6, IL-8, IL-10, IL-17, IL-18. Among them, the causal effect of OSA on IL-5 was almost significant (estimate: 0.267 [-0.030, 0.564], p=0.078). These results were consistent in the sensitivity analysis. Conclusions: Although IL-1β, IL-2, IL-4, IL-6, IL-8, IL-12, IL-17, IL-18 and IL-23 were increasing and IL-10 was reducing in OSA, no significant causal relationships were observed between them by MR analysis. Further research is needed to test the causality of OSA risk on elevated IL-5 levels.